High-intensity bodyweight interval training increases strength and functional capacity in older adults - Gabriela Vitória Gonçalves Evangelista; Fabiana Scartoni; Felício Savioli Neto; Lara Cristina Brandão Consolo Zucareli; André José Aguilar; Alexandre Machado; Danilo S. Bocalini; Francisco Luciano Pontes Júnior (Motricidade)
The present research aimed to analyze the effect of HIIT with body weight on strength and functional capacity parameters in older adults. Sixty sedentary older people were randomized into the control group (n=30) and the training group (n=30), who performed the bodyweight interval training program. The training consisted of 3 weekly sessions of 30 minutes in duration, performed on alternate days, consisting of warm-up, central part, and cool-down. The main part of the training session was 20 minutes long, totalling 20 work cycles. Each work cycle comprised 30 seconds of stimulation and 30 seconds of passive recovery. To verify the functional variables of older adults, the 5-time sit-and-stand test, the 10m walk test, the Timed Up and Go (TUG), and the 1RM test were used to determine maximum muscular strength. The results showed significant differences (p<0.05) for the TUG (p=0.0001), 5TSTS test (p=0.009), and maximum reproduction for elbow flexion 1RMEF (p=0.05) for the group Training. High-intensity interval training with body weight improves the functionality mainly of the lower limbs, impacting the performance of instrumental activities of daily living and gait performance, generating autonomy and independence of movement.